The profound nature of the connection between the impact of using artificial intelligence in retail on buying and the consumers' perceptions of artificial intelligence on the path to the next normal - Theodor Purcărea; Valeriu Ioan-Franc; Ştefan-Alexandru Ionescu; Ioan Matei Purcărea (Amfiteatru Economic Journal, 2021)
The purpose of this paper is to investigate the impact of the use of Artificial Intelligence in retail on buying and consumer behavior, better understanding how consumers perceive Artificial Intelligence on the path to the Next Normal. The consumer-technology partnership is confirming the reinvention of the retail organizations, retailers' advancement on this path involving acting on the new patterns and behaviors by considering the new technology adoption within the context of COVID-19. Based on a comprehensive literature review on the impact of Artificial Intelligence in retail a quantitative research design was employed to demonstrate the nature of linkage between this impact and consumers' perceptions of Artificial Intelligence. The data collection was performed through survey conducted in a supermarket chain in Romania, consumers' perceptions of Artificial Intelligence being considered a central metric for assessing the successful use of Artificial Intelligence-enabled interactions within the context of the offline-online convergence confirmed by the Store of the Future, and consumers' use of mobile phones in their Omni channel shopping journey. The present research, whose results were validated, offers retailers deep consumer insights with regard to the buying and consumer behavior change in Romania on the path to the Next Normal.
Keywords: D12; L81; M31; O33; 330; artificial intelligence; retail; buying and consumer behaviour; consumers' perceptions of artificial intelligence; store of the future; next normal